Effects of two-step golf swing drills on rhythm and clubhead speed in competitive juniors - Mori, K.; North, T. D.; Cheng, K. J.; Baek, S.; Alvis, H. B.; Kwon, Y. H. (Sports Biomechanics, 2025)
Vertical and horizontal rhythms are crucial aspects of a dynamic golf swing, and the two-step swing drills (TSSD) were specifically designed to promote rhythmic unloading and loading of the legs. The purpose of this study was to evaluate the effects of a TSSD training session on the swing rhythm and clubhead speed (CHS) among competitive junior golfers (3.1 ± 4.4 hcp). The driver swings (7 swings each) of 10 competitive junior golfers (aged 15-18) were captured before and after a TSSD session consisting of four stages (lasting less than 45 minutes). Post-TSSD training, there were significant increases in CHS (p < .001), maximum unweighting (p = .006), the trail-side push (p = .009), the horizontal motion ranges of the body and pelvis (p = .005-.031), the upward/downward motion range of the body in the backswing (p = .042/.024), and the backswing/downswing angular velocity peaks of the axle-chain system (p < .033). The stepping-like leg actions primarily facilitated horizontal motion rhythm over vertical motion and unweighting over push in terms of ground interaction. These findings suggest that TSSD can serve as an effective method for developing a rhythmic and dynamic motion pattern while increasing CHS.